2020
DOI: 10.1192/bjp.2020.68
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of smoking on suicidal ideation and attempts: triangulation of epidemiological approaches

Abstract: BackgroundPrevious literature has demonstrated a strong association between cigarette smoking, suicidal ideation and suicide attempts. This association has not previously been examined in a causal inference framework and could have important implications for suicide prevention strategies. AimsWe aimed to examine the evidence for an association between smoking behaviours (initiation, smoking status, heaviness, lifetime smoking) and suicidal thoughts or attempts by triangulating across observational and Mendelia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 53 publications
4
32
0
Order By: Relevance
“…The associations of smoking with depression, schizophrenia 41 , suicide ideation 42 and bipolar disorder 36 have been revealed in previous MR studies. The present study was based on more recent GWASs and comprehensively investigated the causal associations between smoking initiation and psychiatric traits.…”
Section: Discussionmentioning
confidence: 65%
“…The associations of smoking with depression, schizophrenia 41 , suicide ideation 42 and bipolar disorder 36 have been revealed in previous MR studies. The present study was based on more recent GWASs and comprehensively investigated the causal associations between smoking initiation and psychiatric traits.…”
Section: Discussionmentioning
confidence: 65%
“…Hence, researchers have aimed to find causal risk factors, which could inspire improvements of suicide intervention strategies. In this issue of the British Journal of Psychiatry , Harrison et al 1 examined whether tobacco smoking is a causal risk factor for potentially fatal behaviours such as suicidal ideations or attempts. Their aim was to triangulate the available evidence by testing for observational associations and causality.…”
mentioning
confidence: 99%
“…Harrison et al observed cross-sectional associations of all self-reported smoking behaviours with suicide attempts and ideation in 45 825–109 688 UK Biobank participants. 1 Analyses were adjusted for age, gender and socioeconomic status. The strongest association was observed between smoking initiation and suicide attempt (odds ratio, 2.07; 95% CI 1.91–2.26; P < 0.001).…”
mentioning
confidence: 99%
See 2 more Smart Citations